The use of the Prométhée method for personnel selection at a brazilian military organization - Almeida, Marcos Vinicius Passarini de; Rangel, Luis Alberto Duncan (Brazilian Journal of Production Engineering, 2023)
It is known that the personnel selection for a position is one of the main factors for maintaining the competitive advantage of an organization. Considering that it is a complex process, involving several alternatives and criteria, it is desirable to adopt tools that are able to reduce its subjectivity, increase its efficiency and transparency, thus helping decision makers to choose the best alternatives. In this context, this work aims to propose a tool that supports managers in the personnel selection process, using the Multicriteria Decision Support methodology. For this, a case study was carried out in a Military Organization, in which the method chosen to create the tool was PROMÉTHÉE. The created tool provided relevant information that helped the decision-making process regarding the selection of personnel for positions in the organization under study.
Keywords: Personnel selection; Multicriteria Decision-making method; Prométhée